Adjuvant chemotherapy for older adults with breast cancer: making the standard a standard. (September 2009) - Pal, Sumanta Kumar; Mortimer, Joanne
Muss HB, Berry DA, Cirrincione CT et al. : Adjuvant chemotherapy in older women with early-stage breast cancer. N. Engl. J. Med. 360, 2055–2065 (2009). To date, only two prospective trials evaluating adjuvant therapy for breast cancer in older adults have been published. The second and more recent trial, Cancer and Leukemia Group B (CALGB) 49907, provides substantial evidence supporting the use of standard adjuvant chemotherapy regimens (doxorubicin-cyclophosphamide or cyclophosphamide-methotrexate-5-fluorouracil) as opposed to simplified oral regimens (capecitabine). In this trial, both the risk of relapse (hazard ratio: 2.09; 95% CI: 1.38–3.17; p < 0.001) and the risk of death (hazard ratio: 1.85; 95% CI: 1.11–3.08; p = 0.02) were significantly higher with capecitabine compared with standard chemotherapy. The current review explores both the implications and potential caveats of this innovative trial. CALGB 49907 represents a paradigm for further studies of adjuvant cancer therapy in older adults.